PENGARUH KEPEMIMPINAN HIJAU MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BAPENDA KABUPATEN ASAHAN - Boby Anugrah Manurung; Aris Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to determine the simultaneous and partial effects of green leadership, work motivation, and work discipline on employee performance. This type of research is descriptive quantitative with data analysis using multiple linear regression. The sampling technique used is saturated sampling with a total of 68 respondents. Validity and reliability tests were conducted to ensure the research instrument was feasible for use. Multiple linear regression analysis yielded the equation: Y = 10.874 + 0.260X1 + 0.344X2 + 0.389X3. The Ftest results prove that H1 is accepted and H0 is rejected, meaning that simultaneously green leadership, work motivation, and work discipline affect performance with an Fcount (5.949) > Ftable (2.75). The t-test results prove that partially green leadership has a positive and significant effect on performance with a tcount (3.404) > ttable (1.99714), work motivation has a positive and significant effect on performance with a tcount (4.986) > ttable (1.99714), and work discipline has a positive and significant effect on performance with a tcount (3.501) > ttable (1.99714). Based on the tcount value, the work motivation variable is the most dominant factor influencing performance. The R2 test results prove that the adjusted R-square value is 0.581, explaining that the magnitude of the influence generated by green leadership, work motivation, and work discipline on performance is 58.1%, while the remaining 41.9% is influenced by other factors not included in this study.